Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Perusahaan Pada PT. Kawasan Industri Makassar (Persero) - Ines Angreni; Renny Mointi; Nurmega Nurmega (STIKes Ibnu Sina Ajibarang, 2023)
This exploration aims to evaluate the monetary presentation of PT. Makassar Industrial Estate (Persero). The type of examination used in the investigation is quantitative. The data taken care of is the financial statements of PT. Makassar Industrial Estate (Persero) 2019-2021 consisting of monetary records and Benefit and Misfortune Reports. As a result of checking the proportion of liquidity using existing proportions, it can be said to be bad because the company will have difficulty in managing its current obligations. Meanwhile, the proportion of speed must be large in order for the organization to meet its momentary commitments by utilizing organizational resources. The proportion of profitability that should be poor so that the useful life of the organization is decreasing, while the proportion of solvency is large, which generally increases consistently except the Proportion of Liabilities in 2021. This is due to the low level of consumption of the organization starting from the initial investment.